Strategic management to increase the absorption of vocational high school graduates in business, industry and work world: a case study - Dami, Zummy Anselmus (Indonesian Indovisi Institute, 2025)
Previous research focused on program evaluation or industrial needs analysis, while this research focused on implementing industrial classes to increase the absorption of vocational graduates. This study aimed to analyse strategic management's role in increasing the absorption of vocational high school graduates in the business world, industry and work. This research uses qualitative methods with a case study type. The results found four main themes, which include: 1). vision and mission of the industrial class, 2). policies, regulations, and policies in the industrial class in increasing graduate absorption, 3). Learning programs and activities in industrial classes in increasing graduate absorption, and 4) strategic steps taken by schools in industrial class programs in increasing graduate absorption.